A antropofagia como poética do traduzir: diálogos com Oswald de Andrade - Vieira Filho, Edgar Rosa (2017)
The present dissertation aims at discussing the appropriateness of the approximation between the concept of anthropophagy, put forward by Oswald de Andrade (1890-1954) in the Brazilian modernist movement in the 1920’s, and the phenomenon of literary translation, more specifically the translation of poetry. In order to verify the possibility of defining a poetics of translating as anthropophagic, we traced the modernist metaphor/concept back to its creation (1928), going through its first association with the phenomenon of translation, proposed by the Brazilian poet and translator Augusto de Campos in the introduction of his book “Verso, reverso, controverso” (1978), and through the critical-reflexive elaboration carried out by Eneida Maria de Sousa (1985) and Else Ribeiro Vieira (1990), reaching the studies on amerindian perspectivism and shamanism, associated with the translation practice in Helena Martins (2012) and Álvaro Faleiros (2013). We then sought suitability in the traced associations, by analyzing Oswald’s translation of the poem “Hechos pasados” (Canto do passado), by the Chilean poet Arturo Torres-Rioseco (1897-1971), inserted in the collection of translated poems “Arturo Torres-Rioseco: Poesias” (1945). Although Oswald himself never approximated his cannibalistic metaphor to the translation phenomenon, as seen in current reflections in the Translation Studies field, we decided to bring up this discussion, since his attitude and choices as a translator seem to suggest the appropriateness of such association